Influence of a Beaufort Sea Storm Surge on Channel Levels in the Mackenzie Delta - Marsh, Philip; Schmidt, Tania (ARCTIC, 1993)
A storm surge in the Canadian Beaufort Sea during September 1985 resulted in a maximum water level of 1.73 m asl and a maximum surge component of 1.38 m at Tuktoyaktuk. This surge resulted in rises in channel water levels of 1.05 m in the outer delta, 0.66 m in the middle delta and 0.16 m in the upper delta, with the peak water levels at these stations lagging 4, 17, and 21 hours respectively behind the peak water level in the Beaufort Sea. This surge clearly illustrates a number of points. First, throughout the Mackenzie Delta increased water levels resulting from surges must be taken into account when calculating channel discharge from a stage-discharge relationship. Second, storm surges play an important role in the flooding of delta lakes. However, further work is required to illustrate the relative importance of flooding by the Mackenzie River versus storm surge related flooding. Third, the surge of September 1985 illustrates the potential effect of rising sea level. Although this surge cannot be used as a direct analogue for future sea level rise because the dynamics of the system are non-linear, it clearly shows that a rise in sea level would have a major impact on the water level regime of delta channels and lakes. Further work should utilize a numerical simulation model to illustrate the effect of rising sea level on water levels in the Mackenzie Delta.Key words: Mackenzie Delta, storm surge, channel water levels, climate change Une onde de tempête dans la partie canadienne de la mer de Beaufort, qui a eu lieu en septembre 1985, a produit un niveau d'eau maximal de 1,73 m ASL et une composante de houle maximale de 1,38 m à Tuktoyaktuk. Cette houle a fait monter le niveau d'eau du chenal de 1,05 m dans la partie extérieure du delta, de 0,66 m dans la partie médiane, et de 0,16 m dans la partie supérieure, le niveau d'eau optimal à ces divers endroits étant respectivement atteint 4, 17 et 21 heures après l'avoir été dans la mer de Beaufort. Cette houle illustre clairement un certain nombre de points. ...